Mass Activated Droplet Sorting (MADS) Enables High‐Throughput Screening of Enzymatic Reactions at Nanoliter Scale. (28th January 2020) - Holland‐Moritz, Daniel A.; Wismer, Michael K.; Mann, Benjamin F.; Farasat, Iman; Devine, Paul; Guetschow, Erik D.; Mangion, Ian; Welch, Christopher J.; Moore, Jeffrey C.; Sun, Shuwen; Kennedy, Robert T.
Abstract: Microfluidic droplet sorting enables the high‐throughput screening and selection of water‐in‐oil microreactors at speeds and volumes unparalleled by traditional well‐plate approaches. Most such systems sort using fluorescent reporters on modified substrates or reactions that are rarely industrially relevant. We describe a microfluidic system for high‐throughput sorting of nanoliter droplets based on direct detection using electrospray ionization mass spectrometry (ESI‐MS). Droplets are split, one portion is analyzed by ESI‐MS, and the second portion is sorted based on the MS result. Throughput of 0.7 samples s −1 is achieved with 98 % accuracy using a self‐correcting and adaptive sorting algorithm. We use the system to screen ≈15 000 samples in 6 h and demonstrate its utility by sorting 25 nL droplets containing transaminase expressed in vitro. Label‐free ESI‐MS droplet screening expands the toolbox for droplet detection and recovery, improving the applicability of droplet sorting to protein engineering, drug discovery, and diagnostic workflows. Abstract : Ein Mikrofluidiksystem zur Sortierung von Nanolitertröpfchen basierend auf Massenspektrometrie erreicht eine vollautomatische markierungsfreie Sortierung bei 0.7 Proben s −1 mit 98 % Genauigkeit. Die In‐vitro‐Transkription und ‐Translation (ivTT) eines Transaminase‐Enzyms in Proben von etwa 25 nL wird demonstriert, und die Proben werden nach ihrer Enzymaktivität sortiert.